Seasonal nutrients variation, eutrophication pattern, and Chlorophyll a response adjacent to Guangdong coastal water, China - He, Yingxian; Zhang, Peng; Xu, Fang; Zhao, Lirong; Zhang, Jibiao (Frontiers in Marine Science, 2023)
Nutrients were the key biogenic elements for the primary production in coastal water, and the increase of nutrient concentration led to eutrophication and frequent occurrence of harmful algal blooms. However, the seasonal nutrients variation, eutrophication pattern, and Chlorophyll a (Chl-a) response adjacent to Guangdong coastal water were still scarcely. In this study, to clarity the seasonal nutrients variation, eutrophication pattern, and Chl-a, response adjacent to coastal water, the spatiotemporal dissolved inorganic nitrogen (DIN) and phosphorus (DIP) patterns and Chl-a were explored by field observation using 52 stations in the coastal waters of Guangdong Province during the dry (April and May), wet (July and August) and normal (October and November) seasons in 2020. The results showed that the variability of Chl-a, DIN and DIP were significantly different in seasons (P<0.01), and the mean concentrations of Chl-a, DIN and DIP were 11.97 ± 28.12 μg/L, 25.84 ± 35.72 μmol/L and 0.59 ± 0.71 μmol/L.Among them, the mean value of Chl-a increased significantly from 9.99 ± 9.84 μg/L in the dry season to 18.28 ± 38.07 μg/L in the wet season, and then decreased significantly to 7.65 ± 27.64 μg/L in the normal season.The mean DIN value decreased significantly from 30.68 ± 43.58 μmol/L in the dry season to 21.91 ± 35.45 μmol/L in the wet season, and then increased to 24.91 ± 26.12 μmol/L in the normal season. the mean DIP value decreased from 0.58 ± 0.73 μmol/L in the dry season to 0.48 ± 0.65 μmol/L in the wet season and then increased significantly to 0.70 ± 0.73μmol/L in the normal season. In addition, the DIN and DIP concentrations at most monitoring stations met the Grade II national seawater quality standards, and only a few monitoring stations fail to meet the Grade IV national seawater quality standard. The DIN/DIP ratios ranged from 2.05 to 259.47, with an average of 43.77 ± 41.01, far exceeding the Redfield ratio, indicating the presence of P limitation in the nearshore waters of Guangdong Province. Besides, the EI values in the coastal waters of Guangdong Province are higher at 0.00 and 82.51, with an average of 4.16 ± 10.90. DIN and DIP were significantly and positively correlated with COD in each season (P<0.05). Moreover, DIN/DIP showed significantly positive correlations with Chl-a in all seasons (P<0.01), indicating that high Chl-a concentrations could be sustained by the nutrients supply in marine ecosystems. Therefore, it is necessary to strengthen the integrated management of land and sea and effectively mitigate regional estuarine and coastal water eutrophication and harmful algal blooms.